1995
DOI: 10.1111/j.1095-8649.1995.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on life history variables in perch

Abstract: Population structure, recruitment, mortality, life expectancy, age at maturity, gonad development, fecundity, net reproductive rate and energy storage were studied in a perch population exposed to thermal discharge. The experiment was conducted during 1978-1990 in an artificial enclosure at a nuclear power plant on the Baltic Sea coast. Abundance increased after the plant started operating, although the proportion of larger perch dropped to a low level. Recruitment improved, but adult mortality increased. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 13 publications
0
55
0
2
Order By: Relevance
“…Many studies have shown that fish in warmer waters mature at a younger age (Sandstrom et al 1995, Morgan & Colbourne 1999, Grift et al 2003. However, for southern Grand Bank cod, both low and high temperatures resulted in earlier maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that fish in warmer waters mature at a younger age (Sandstrom et al 1995, Morgan & Colbourne 1999, Grift et al 2003. However, for southern Grand Bank cod, both low and high temperatures resulted in earlier maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Wild European perch (N=22) were caught by hook and line in the Biotest enclosure (∼1 km 2 ), a man-made enclosure in the Baltic Sea receiving heated water from the cooling system of the nuclear power plant in Forsmark, Sweden (Hillebrand et al, 2010;Sandstrom et al, 1995). Fish were transported by road (<1 km) to a field laboratory and separated randomly between two 1000 l tanks containing air diffusers and flowthrough seawater pumped from the Biotest enclosure (23±1°C; salinity 5 ppt).…”
Section: Experimental Animals and Holding Conditionsmentioning
confidence: 99%
“…For example, in populations of one perch species {Perca flavescens) experiencing elevated water temperatures simultaneously with poor feeding conditions, the perch adopted an energy-saving strategy. The perch reduced clutch size or stopped egg production entirely in the year(s) following the year of first reproduction; this strategy reduced the high mortality risk associated with the considerable energy investment into gamete production (Jansen, 1996;Sandstrom et al, 1995). Delayed sexual maturity could be an energy-saving strategy in Sonoran females, together with the tendency to produce only one clutch or even no clutches as a response to unfavorable environmental conditions (Averill-Murray et al, 2002b).…”
Section: Growth Strategies Ecological Implications and Conclusionmentioning
confidence: 99%